HUBUNGAN UMUR IBU DENGAN KEJADIAN KOMPLIKASI PADA KEHAMILAN - SARIDEWI, WISDYANA (JURNAL KESEHATAN KARTIKA, 2021)
Pregnancy is a natural and physiological process. However, not all pregnancy processes are normal. Some pregnant women experience pregnancy complications. Pregnancy complications can occur in the first, second or third trimester. Pregnancy complications can be influenced by factors outside of pregnancy, one of which is the mother's age. Pregnant women who are too young (<20 years) in terms of uterine anatomy and physiology have not grown optimally. Pregnant women who are too old (> 35 years) are at risk because body functions are aging and the birth canal gets stiffer. The purpose of this study was to analyze the relationship between maternal age and pregnancy complications. This research used analytic observational research method with cross sectional research design. This study uses secondary data with a sample of pregnant women who experience pregnancy complications. The results showed that most of the mothers who experienced pregnancy complications were at the age of 20-35 years (65%), the most common complication in pregnancy was abortion followed by severe preeclampsia and there was no relationship between the age of the mother and the incidence of pregnancy complications.